18 the willingness to pay of air travel passengers to offset their carbon dioxide (CO2) emissions: a Putrajaya resident case study - Fatihah, S. Nur; Rahim, A. S. Abdul (Journal of Tourism, Hospitality and Environment Management, 2017)
Nowadays, demand for air transportation has increased tremendously. The rise in airline flight will increase the amount of carbon dioxide (CO2) released into the atmosphere. Some countries are developing strategies to reduce CO2 emissions from aviation, and Malaysia’s target is to reduce CO2 emissions by 45% by the year 2030. Consequently, this study investigated whether Malaysian air travellers are willing to pay for an increase in their travel cost to reduce the carbon emissions from their flight to minimize the environmental impact. Using the contingent valuation method of double-bounded dichotomous choice format and a survey of 250 Putrajaya residents’ to gage their willingness to pay (WTP) for airline carbon offsets, where the majority of people travel by airplane, instead of driving cars for a long travel distance. The results reveal that the WTP is RM6.10 per person; income and age were found to have a significant relationship with WTP. Hence, this scheme can be realized if the Malaysian air travellers, especially the respondents from Putrajaya, cooperate by paying extra money for a “Carbon Neutral Fund” to protect and rehabilitate our environment from being polluted by aviation activities. Policy implications of the findings are discussed, encouraging aviation industries and policy makers to implement greater voluntary climate action.